Magnetic Assisted Finishing of Internal Surfaces - Munish Kumar; Ajay Choudhary; Dilshad Ahmad Khan (Engineering Proceedings, 2024)
Surface quality is one of the most important things to think about when using precision equipment. Inadequate surface quality in engineering products can result in a number of issues, such as excessive wear, failures, improper geometry, and more. Traditional finishing techniques are neither flexible nor economical when it comes to finishing complex geometries. When it comes to finishing with low tolerances and no surface topography degradation, magnetic assisted finishing systems rank among the best. This chapter discusses the types of magnetic assisted finishing techniques, including BERMP, UAMAF, and MAF, and how they are used to finish internal surfaces.